Global aging exacerbates heat exposure risk across diverse socioeconomic pathways - Xiao Chen; Song Leng; Zhaowu Yu; Ranhao Sun (Geography and Sustainability, 2025)
Elderly individuals disproportionately face heat exposure risk compared to other demographic groups, with projected amplification in the future. The vast disparities between Global North and South countries necessitate a comprehensive understanding of the underlying factors influencing future heat exposure vulnerabilities. Here, we use factor decomposition method to quantify the contribution of climate change, population, and aging to heat exposure risk under four shared socioeconomic pathways (SSP) (SSP126, SSP245, SSP370, SSP585) from 2000 to 2100 at 20-year intervals. Results demonstrate a projected global escalation in heat exposure risk by 16 and 76 times under SSP126 and SSP585, respectively, with the North generally suffering lower risk than the South. Climate change emerges as a pivotal driver of future heat exposure risk in the North while aging notably influences the South. Despite climate change is projected to reduce heat exposure risk by up to 10 % in the North under SSP1-2.6 by the end of the 21st century, aging remains a critical risk factor.